'Scan-negative' cauda equina syndrome: what to do when there is no neurosurgical cause. Issue 1 (13th August 2021) - Hoeritzauer, Ingrid; Stanton, Biba; Carson, Alan; Stone, Jon
Abstract : Suspected cauda equina syndrome is a common presentation in emergency departments, but most patients (≥70%) have no cauda equina compression on imaging. As neurologists become more involved with 'front door' neurology, referral rates of patients with these symptoms are increasing. A small proportion of patients without structural pathology have other neurological causes: we discuss the differential diagnosis and how to recognise these. New data on the clinical features of patients with 'scan-negative' cauda equina syndrome suggest that the symptoms are usually triggered by acute pain (with or without root impingement) causing changes in brain–bladder feedback in vulnerable individuals, exacerbated by medication and anxiety, and commonly presenting with features of functional neurological disorder.